UPAYA KEPALA MI MUHAMMADIYAH PANDEAN DALAM PENINGKATAN MOTIVASI KERJA GURU - Sumarno Sumarno (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2024)
This study aims to describe the efforts of the principal of MI Muhammadiyah Pandean in improving teachers’ work motivation. Teachers’ work motivation is an important factor in determining the quality of learning, discipline, professionalism, and the achievement of educational goals. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing. The findings show that the principal’s efforts to improve teachers’ work motivation were carried out through five main strategies: giving rewards to outstanding teachers, providing motivational guidance through regular meetings, creating a conducive work environment, strengthening interpersonal communication, and applying a family-based approach in problem solving. These strategies positively contributed to improving teachers’ work spirit, discipline, loyalty, responsibility, and professionalism. The principal played a role as a motivator, mentor, communicator, and leader who was able to create a harmonious work culture oriented toward improving educational quality.